The Typology of Urban Polycentricity: A Comparative Study of Firm Distribution in 35 Chinese Cities - Zhihui Wu; Yanyan Peng; Bo Qin (Urban Science)
Prevailing theories and empirical studies have suggested that the internal spatial structures of large cities have transformed from monocentric to polycentric. However, the existing literature primarily focuses on the definition, measurement, and quantity of the urban centers, with a lack of in-depth comparison of urban polycentricity in terms of dynamic centralization or dispersion. By analyzing the spatial distribution of firms in 35 large Chinese cities, this study examines the quantity, centralization degree, and primacy ratio of urban centers to compare spatial structure of the cities and explores the different types of urban polycentricity by employing nonparametric regression methods. The findings indicate that the spatial structures of most cities are polycentric forms, which display three types: emerging polycentricity, centralized polycentricity, and dispersed polycentricity. Further analyses suggest that social and economic factors such as GDP and population size are associated with the typology. Through the comparison of the 35 cities’ spatial structures, this study identifies three types of urban polycentricity and sheds light on the underlying forces of urban spatial restructuring process.